2022
DOI: 10.3390/ijerph19074165
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends of Nutrition in Cancer Research: A Bibliometric and Visualized Analysis Study over the Past 10 Years

Abstract: The increasing application of nutrition in cancer management has attracted a great deal of research interest in recent decades. Nutritional therapies, interventions, and assessments were known to have positive effects on reducing side effects from cancer therapy. In order to identify the global research output for nutrition in cancer research, a bibliometric analysis during the past 10 years was conducted to evaluate the current status of trends, gaps, and research directions as no bibliometric studies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The global trend of research in the field of nutrition in cancer is gradually increasing 26. To date, there is evidence that an individualised nutritional support reduces the risk of mortality and improves QoL in patients with cancer at malnutritional risk 27.…”
Section: Discussionmentioning
confidence: 99%
“…The global trend of research in the field of nutrition in cancer is gradually increasing 26. To date, there is evidence that an individualised nutritional support reduces the risk of mortality and improves QoL in patients with cancer at malnutritional risk 27.…”
Section: Discussionmentioning
confidence: 99%
“…The title-only search may, in fact, result in the loss of some documents (false negative); however, the error (false positive) resulting from “TOPIC” is greater ( 19 ). Furthermore, the title-only search approach adopted in this study has been validated and applied in previous research ( 19 – 21 , 24 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The development of bibliometric tools such as the R package "Bibliometrix" (Arruda et al, 2022) and the software packages "CiteSpace" (Liu et al, 2022) and "VOSviewer" (Huang et al, 2022) makes visual analysis of documents more convenient. These programs have been widely used in various fields, such as medicine (Youn et al, 2022), climate (Han et al, 2022), materials science (Sun et al, 2022), and others. In recent years, studies have indicated that using 3D printing bioink to treat bone tissue defects has good prospect, however bibliometric evaluation of this valuable field is currently lacking.…”
Section: Advantages Of Bibliometric Analysismentioning
confidence: 99%